EFEKTIFITAS PEMBERIAN PENYULUHAN KESEHATAN TENTANG INISIASI MENYUSU DINI TERHADAP PERILAKU IBU DALAM MENYUSUI DINI - Nina Fitri; Bunga Mustia Yendri (Maternal Child Health Care, 2022)
EBI is important in the success of breastfeeding and exclusive breastfeeding, but 87% of infants in Indonesia do not have EBI.in the working area of the Bonjol Health Center, Pasaman Regency,in 2020 only 44.98% of infants experienced EBI. This study to determine the effectiveness of providing health education about early initiation of breastfeeding (EBI) on the behavior of mothers in early breastfeeding at the Bonjol Public Health Center, Pasaman Regency in 2022. Post-test test design approach. The population in this study were pregnant women in the third trimester . Sampling using quota sampling technique with a sample of 10 people. Collecting data in this study used knowledge and attitude questionnaires and observations of EBI actions. Data analysis includes univariate analysis and bivariate analysis using the Wilcoxon test. The results showed that the average knowledge of respondents about EBI pre-test was 3.3 and post-test was 7.4, the average attitude of the pre-test was 26.7 and post-test was 34.7, and the average the mean of the pre-test was 3.4. and posttest 10.7. There is a difference in the average knowledge of pretest and posttest with an average rank of 5 and p = 0.007, there is a difference in the average attitude of pretest and posttest with an average rank of 5 and p = 0.007 and there is a difference in the average pre-test and post-test measurements with mean rank 5 and p = 0.007. It can be concluded that the provision of health education about early initiation of breastfeeding is effective in increasing EBI behavior. Therefore, it is hoped that all parties, especially health workers, always provide education about EBI in antenatal care services as an effort to prepare mothers for EBI action. Keywords: Counselling, EBI, Behavior